Testing children for allergies: why, how, who and when: An updated statement of the European Academy of Allergy and Clinical Immunology (EAACI) Section on Pediatrics and the EAACI‐Clemens von Pirquet Foundation. Issue 2 (18th March 2013) - Eigenmann, P. A.; Atanaskovic‐Markovic, M.; O'B Hourihane, J.; Lack, G.; Lau, S.; Matricardi, P. M.; Muraro, A.; Namazova Baranova, L.; Nieto, A.; Papadopoulos, N. G.; Réthy, L. A.; Roberts, G.; et al.
Abstract: Allergic diseases are common in childhood and can cause a significant morbidity and impaired quality‐of‐life of the children and their families. Adequate allergy testing is the prerequisite for optimal care, including allergen avoidance, pharmacotherapy and immunotherapy. Children with persisting or recurrent or severe symptoms suggestive for allergy should undergo an appropriate diagnostic work‐up, irrespective of their age. Adequate allergy testing may also allow defining allergic trigger in common symptoms. We provide here evidence‐based guidance on when and how to test for allergy in children based on common presenting symptoms suggestive of allergic diseases. Abstract :